METTL3-Mediated m6A Modification Regulates the Osteogenic Differentiation through LncRNA CUTALP in Periodontal Mesenchymal Stem Cells of Periodontitis Patients - Xin Chen; Yuan Qin; Xian Wang; Hao Lei; Xiaochen Zhang; Houzhuo Luo; Changgang Guo; Weifu Sun; Shishu Fang; Wen Qin; Zuolin Jin (Stem Cells International)
Objective. Periodontitis is a chronic inflammatory disease that causes loss of periodontal support tissue. Our objective was to investigate the mechanism by which METTL3-mediated N6-methyladenosine modification regulates the osteogenic differentiation through lncRNA in periodontal mesenchymal stem cells in patients with periodontitis (pPDLSCs). Material and Methods. We carried out a series of experiments, including methylated RNA immunoprecipitation-PCR, quantitative real-time polymerase chain reaction, and western blotting. The expressions of alkaline phosphatase (ALP), Runx2, Col1, Runx2 protein level, ALP staining, and Alizarin red staining were used to demonstrate the degree of osteogenic differentiation. Results. We found that METTL3 was the most significantly differentially expressed methylation-related enzyme in pPDLSCs and promoted osteogenic differentiation of pPDLSCs. METTL3 regulated the stability and expression of lncRNA CUTALP, while lncRNA CUTALP promoted osteogenic differentiation of pPDLSCs by inhibiting miR-30b-3p. At different time points of osteogenic differentiation, lncRNA CUTALP expression was positively correlated with Runx2, while miR-30b-3p showed the opposite pattern. The attenuated osteogenic differentiation induced by METTL3 knockdown was recovered by lncRNA CUTALP overexpression. The attenuated osteogenic differentiation induced by lncRNA CUTALP knockdown could be reversed by the miR-30b-3p inhibitor. Conclusions. In summary, METTL3/lncRNA CUTALP/miR-30b-3p/Runx2 is a regulatory network in the osteogenic differentiation of pPDLSCs.